2020
DOI: 10.1155/2020/8883839
|View full text |Cite
|
Sign up to set email alerts
|

Does Measurement of Corticospinal Tract Involvement Add Value to Clinical Behavioral Biomarkers in Predicting Motor Recovery after Stroke?

Abstract: Background. The prediction of motor recovery after stroke is an important issue, and various prediction models have been proposed using either clinical behavioral or neurological biomarkers. This study sought to identify the effects of clinical behavioral biomarkers combined with corticospinal tract (CST) injury measurement on the prediction of motor recovery after stroke. Methods. The region of interest was drawn on the normalized brain magnetic resonance imaging scans of patients with first-ever unilateral h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Though a subset of patients with stroke with affected corticospinal tract integrity does not demonstrate MEP with the highest stimulation intensity, taking RMT as 100% could affect the decrease in RMT post-therapy in the RG group. However, critical studies like Hendrics et al and Jong et al have established MEP as a sensitive and valid prognostic marker of motor recovery after stroke [ 61 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though a subset of patients with stroke with affected corticospinal tract integrity does not demonstrate MEP with the highest stimulation intensity, taking RMT as 100% could affect the decrease in RMT post-therapy in the RG group. However, critical studies like Hendrics et al and Jong et al have established MEP as a sensitive and valid prognostic marker of motor recovery after stroke [ 61 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was the first study in patients with AIS to use a non-inferiority trial design to evaluate the efficacy of The MCID for the FMA was 6.6 and 6 points for the upper and lower extremity respectively. 40 We assumed that the δ of the FMA was 12, which was below the MCID. Research has shown that the MCID values for the ARAT were 12 and 17 points for upper extremity standardized measures early post-stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the threshold were most likely due to the intervention received rather than inter-session variability as MEPs, which were acquired at two time points with an interval of 31 days: day 1 (pre-therapy) and day 32 (post-therapy) ( 10 13 ). Moreover, critical studies like that by Hendrics et al, and Jong et al, have established MEP as a sensitive and valid prognostic marker of motor recovery after stroke ( 14 16 ). For cortical-excitability to be increased in the ipsilesional-hemisphere for patients with stroke (after recovery), the ipsilesional-RMT should be decreased from pre-to-post-therapy and hence, normalization or RMT ratio (RMT Ipsilesional/RMT contralesional) should decrease to approach normalization ( 17 20 ).…”
Section: Discussionmentioning
confidence: 99%